Microwave assisted synthesis and antimicrobial activity of Fe3O4-doped ZrO2 nanoparticles. Issue 8 (1st June 2019) - Imran, M.; Riaz, Saira; Sanaullah, Ifra; Khan, Usman; Sabri, Anjum N.; Naseem, Shahzad
Abstract: Composites play important role in dental filling by controlling shrinkage along with correction in teeth's shape and position. Rehabilitation of severely worn dentition can be achieved using mechanically strong composites. This study aims to synthesize zirconia-based composites to be used as dental fillers. Effect of microwave powers (100–900 W) along with Fe3 O4 doping are studied on the structural, mechanical and magnetic properties of stabilized zirconia. SEM and TEM reveal formation of spherical nanoparticles with diameter of ∼30 nm. XRD results shows phase pure tetragonal zirconia (t-ZrO2 ) at microwave power of 500 W without any post heat treatment. Crystallite size calculated from XRD data (∼23 nm) matches well with the previously reported value for stabilization of t-ZrO2 . Microwave energy dissipation results in stresses causing volume shrinkage leading to monoclinic to tetragonal phase transformation with higher X-ray density and hardness of ∼1347HV. VSM results show ferromagnetic response with low coercivity (600Oe) value and saturation magnetization (∼2emu/g). It is worth mentioning here that this is one of its kind study reporting synthesis of room temperature stabilized Fe3 O4 doped zirconia composites at microwave power of 500 W. Antibacterial studies reveal inhibition zone of ∼32 mm against bacillus bacteria suggesting their potential use as dental filler.